The Relationship Between Work Culture And Employee Performance: Mediation Of Job Satisfaction And Moderation Of Leadership In Bank BJB Syariah - Tri Utami Handayani; Moh. Mukhsin (Economics and Business Journal (ECBIS), 2026)
This study examines work culture, job satisfaction (mediator), and leadership (moderator) as predictors of employee performance at PT Bank BJB Syariah Serang Branch, where average KPI achievement stood at only 90.5% in 2024. A census survey of all 190 employees was analyzed using PLS-SEM via SmartPLS.The results show: (1) work culture is positively associated with employee performance (β = 0.512, p < .001); (2) work culture is positively associated with job satisfaction (β = 0.991, p < .001); (3) job satisfaction is positively associated with employee performance (β = 0.160, p < .001); (4) job satisfaction partially mediates the work culture–performance relationship (β = 0.159, p < .001); and (5) leadership significantly moderates the work culture–performance relationship with a buffering effect (p < .001). This study extends JD-R Theory to faith-based organizations by demonstrating that Islamic values reshape job resources: work culture becomes a dominant predictor of satisfaction, and leadership operates as a buffering moderator through substitution mechanisms. These findings highlight the strategic importance of strengthening Islamic work culture, effective leadership, and job satisfaction as key predictors of employee performance in Islamic banking.